Subgrade Feasibility Analysis for Tourist Access Roads in Senggani Gorge, Tulungagung Using Laboratory CBR Testing - Cahyono, Andri Dwi; Mahardana, Zendy Bima; Dewanta, Rendy Kurnia; Hidiyati, Evita Fitrianis; Rivianto, Arif (Universitas Negeri Padang, 2024)
Highways have an important role in the economic and tourism sectors, providing easy accessibility and accelerating regional growth. Senggani Gorge, a tourist attraction in Nglurup Hamlet, Sentang District, Tulungagung Regency, is the main attraction with the charm of waterfalls and natural coffee plantations in the highlands. However, accessibility constraints arise because the path to the tourist attraction is still slippery and bumpy clay. Clay soil conditions pose access difficulties, so more research is needed to understand the potential use of clay soil as a base layer of road pavement. This study focused on a research system that involved soil sampling on the access road to Senggani Gorge. Experimental methods were used to evaluate the effect of using clay subgrades on such tourist road access. The laboratory CBR test was conducted to test the strength of clay subgrade in road pavement construction, with the main aim to determine the impact of its use on tourist access to Senggani Gorge in Tulungagung. The results showed the percentage of CBR in collision variations 10, 25, and 56, as well as a comparison with research in Nglurup Hamlet which reached a CBR value of 27%. These findings are expected to provide a dimension of comparison and generalization of results, broadening understanding of the use of clay soils as road construction materials in various locations.